Thin Layer Coulometry with Ionophore Based Ion-Selective Membranes - Grygolowicz-Pawlak, Ewa; Bakker, Eric (American Chemical Society, 2010)
We are demonstrating here for the first time a thin layer coulometric detection mode for ionophore based liquid ion-selective membranes. Coulometry promises to achieve the design of robust, calibration free sensors that are especially attractive for applications where recalibration in situ is difficult or undesirable. This readout principle is here achieved with porous polypropylene tubing doped with the membrane material and which contains a chlorinated silver wire in the inner compartment, together with the fluidically delivered sample solution. The membrane material consists of the lipophilic plasticizer dodecyl 2-nitrophenyl ether, the lipophilic electrolyte ETH 500, and the calcium ionophore ETH 5234. Importantly and in contrast to earlier work on voltammetric liquid membrane electrodes, the membrane also contains a cation-exchanger salt, KTFPB. This renders the membrane permselective and allows one to observe open circuit potentiometric responses for the device, which is confirmed to follow the expected Nernstian equation. Moreover, as the same cationic species is now potential determining at both interfaces of the membrane, it is possible to use rapidly diffusing and/or thin membrane systems where transport processes at the inner and outer interface of the membrane do not perturb each other or the overall composition of the membrane. The tubing is immersed in an electrolyte solution where the counter and working electrode are placed, and the potentials are applied relative to the measured open circuit potentials. Exhaustive current decays are observed in the range of 10 to 100 μM calcium chloride. The observed charge, calculated as integrated currents, is linearly dependent on concentration and forms the basis for the coulometric readout of ion-selective membrane electrodes.